SISTEM INFORMASI PENGUMUMAN AKADEMIK BERBASIS WEB DENGAN FASILITAS SMS GATEWAY DI MA PANDANARAN - , HARIS SHOLEH PRAKOSO, Agus Sihabudin, S.Si., M.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Developments in information technology today growing very rapidly together with the requirement for speed and accuracy an information system. Academic information is one of the most important requirement in the school. In MA (Madrasah Aliyah) Pandanaran is still use manual way to disseminate academic information. At first Teachers make the letter and then distributed one by one in each class. the result is takes a lot of time and worker to disseminate information. In addition in the dissemination of information contained that do not know or too late to find out information. Web based Academic announcements information With SMS Gateway facilities in MA Pandanaran, designed to provide ease of the school concerned to disseminate information to students, and guardians of students effectively and efficiently. This system uses the PHP programming language, the MySQL to manage the database, and Gammu to Gateway SMS facilities. The system is designed to manage student data, guardians of students, and school staff in MA Pandanaran. The data is processed by the admin then used to disseminate academic information. Admin wrote information content, delivery time, and destination of the recipient to be sent via the SMS service.